2019
DOI: 10.4084/mjhid.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Vitamin D Receptor Genetic Variants in Egyptian Children With Beta Thalassemia on Vitamin D Supplementation

Abstract: BackgroundLow bone mineral density (BMD) is a characteristic feature of Beta thalassemia major (βTM) patients. Vitamin D is important for bone mineralization. Vitamin D receptors (VDR) genetic variants may be related to vitamin D status and BMD.ObjectivesTo evaluate the effect of VDR genetic variants on vitamin D levels and BMD in βTM Egyptian patients supplemented with vitamin D.MethodsThis study was conducted on forty children with βTM and seventeen unrelated healthy sex and age-matched controls. Serum calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…It is worth noting that our findings with that of Abbassy et al, 27 who found associations of some VDR genetic variants (i.e., BsmI bb, FokI Ff, and ff) with BMD changes and occurrence of osteoporosis in the same type of population, confirm and support vitamin D metabolic-axis genetic variants implication in BMD of pediatric Egyptian β-thalassemia patients.…”
Section: Discussionsupporting
confidence: 89%
“…It is worth noting that our findings with that of Abbassy et al, 27 who found associations of some VDR genetic variants (i.e., BsmI bb, FokI Ff, and ff) with BMD changes and occurrence of osteoporosis in the same type of population, confirm and support vitamin D metabolic-axis genetic variants implication in BMD of pediatric Egyptian β-thalassemia patients.…”
Section: Discussionsupporting
confidence: 89%
“…Vitamin D is involved in several non-skeletal functions, such as cell regulation, differentiation, and growth 3 , and adaptive and innate immunity control 5 , as well as being associated with inflammatory markers 6 , since the vitamin D receptor ( VDR ) is expressed in almost all human cells 7 . The activity of this nutrient in the human organism involves its binding with VDR 8 , whose expression is modulated by the blood levels of the 1,25diidroxi-vitamin D (1,25 (OH) 2D) 9 and genetic variants 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The immune-related vitamins and minerals, including vitamin C [ 9 ], vitamin E [ 9 , 14 ], vitamin D [ 15 ], zinc [ 9 , 16 ] and selenium [ 9 , 17 ], were identified to be reduced among patients with β-thalassemia when compared with healthy controls. Only one study by El Missiry et al reported normal levels of zinc among 30 patients, which was comparable with healthy control [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study by El Missiry et al reported normal levels of zinc among 30 patients, which was comparable with healthy control [ 18 ]. Interestingly, the mean level of 25-OHD 3 in β-thalassemia and healthy controls was lower than the sufficient reference value [ 15 ]. A similar finding was observed regarding selenium [ 9 , 17 ] and in zinc [ 16 ] indicating that these reduced vitamins and minerals might not only be affected by the disease status or severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation